Estimation and Economic Valuation of Above-Ground Carbon in Forest Area with the Special Purpose of Gunung Bromo, Karanganyar, Central Java, Indonesia - Rissa Rahmadwiati; Rezky Lasekti Wicaksono; Dwi Apriyanto (Jurnal Sylva Lestari, 2022)
Climate change and the increasing greenhouse effect are serious problems of global concern today. The existence of forests plays an essential role in carbon sequestration and storage to reduce greenhouse gas (GHG) concentration in the atmosphere. Forest Area with the Special Purpose (KHDTK) of Gunung Bromo has an area of 126,291 ha that is designated as an educational forest. The area has been managed by Universitas Sebelas Maret since 2019 and consists of three main tree species, namely Pinus merkusii, Swietenia mahagoni, and Dalbergia latifolia. This study aims to estimate the potential uptake and economic valuation of carbon stocks in the KHDTK of Gunung Bromo. Stratified Systematic Sampling with Random Start was used as an inventory method in this study. The estimation of above-ground carbon uptake used general allometric equations (non-destructive method). Furthermore, the carbon economy valuation referred to the range of calculating the average carbon price for each program specification. The results showed that the estimated carbon of tree stands in KHDTK of Gunung Bromo reached 75.81 tonnes C/ha with a carbon economic valuation of USD 758.1/ha or equivalent to IDR 10,856,863.80/ha. Exploring the potential for biodiversity (flora and fauna) and environmental services such as carbon sink will support the ecotourism program in KHDTK of Gunung Bromo. Keywords: biomass, carbon estimation, economic valuation, KHDTK of Gunung Bromo